Could IGF-I levels play a neuroprotective role in patients with large vestibular schwannomas?. (10th November 2017) - Fotakopoulos, George; Fountas, Kostas; Tsianaka, Eleni; Kotlia, Polikceni; Pachatouridis, Dimitrios; Paschalis, Thanos; Voulgaris, Spyridon
Aim: To evaluate the possible superiority of outcome in patients with elevated IGF-I levels after vestibular schwannoma (VS) resection.Patients & methods: This retrospective study included 65 patients (34 male, 52.3%) with VS operated in between January 2009 and April 2014 (follow-up 3.2 ± 0.7 years). Preoperative or postoperative IGF-I levels were identified for each patient.Results: Patients were divided into two groups: Group A (small size tumor), 56 patients; and Group B (large size tumor), 9 cases. IGF-I levels in Group A (195.8 ± 32.9 ng/ml) were compared with those of Group B (242.2 ± 22.2 ng/ml) and were found to have statistically significant difference (p = 0.001).Conclusion: Increased IGF-I levels could hold a key role in nerve recovery in patients undergoing surgical resection of large VS. Lay abstract: The aim of this study was to examine the possible correlation between IGF-I levels in serum in large vestibular schwannomas (VS) and its potential neuroprotective effect on the vestibulocochlear nerve. This retrospective study included 65 patients that underwent surgery, 9 of whom were diagnosed with large VS. Results suggested that elevated IGF-I in serum levels could help identify patients with large VS with better neuroprotective activity.